Efficacy of EA575 as an Antitussive and Mucoactive Agent in Preclinical In Vivo Models - Matthias Hufnagel; André Rademaekers; Anika Weisert; Hanns Häberlein; Sebastian Franken (Biomedicines)
Background: The efficacy of EA575 in the treatment of respiratory diseases is described in various clinical studies, improving patients’ disease-related symptoms. However, mechanistic in vivo data proving its beneficial effects are limited. Methods: Focusing on the treatment of acute airway inflammation and accompanying cough, this study aimed to elucidate antitussive and mucoactive properties of EA575, applying two animal models. Animals were treated orally twice daily for 7 days, resulting in 43, 215.2, or 430.5 mg/kg bw/d of EA575. Antitussive effects were investigated within an acute lung inflammation model of bleomycin-treated guinea pigs after citric acid exposure. Hereby, the number of coughs, enhanced pause (penH), and bronchoalveolar lavage fluid (BALF) were investigated. Mucoactivity of EA575 was assessed within a murine model, determining phenol red concentration in BALF. Results: EA575 treatment within the acute lung inflammation model reduced cough events up to 56% while reducing inflammatory cell influx in BALF dose-dependently, e.g., reducing neutrophils in BALF up to 70.9%. This suggests a strong connection between anti-inflammatory and antitussive properties of EA575. Furthermore, penH decreased in a dose-dependent manner, suggesting an ease in respiration. Mucoactivity was shown by a dose-dependent increase in phenol red concentration in BALF up to 38.9%. Notably, EA575/salbutamol co-administration resulted in enhanced phenol red secretion compared to respective single administrations. Conclusions: These data highlight the benefits of EA575 in treating cough-related respiratory diseases, particularly when accompanied by sputum, as EA575 has been shown to obtain mucoactivity. Furthermore, the combinatory effect of EA575/salbutamol treatment provides a foundation for future research in the treatment of chronic respiratory diseases.